Characteristics of water absorption capacity of weathered sandstone based on nuclear magnetic resonance and wave velocity testing - Ran NIU; Xiaowei JIANG; Yongshuai YAN; Kaigao OUYANG; Xianchun SUN; Hongbin YAN; Li WAN (Shuiwen dizhi gongcheng dizhi)
Water is a key factor in the weathering and erosion of rocks, and highly porous rocks are generally more susceptible to weathering. However, there has been a lack of in-situ methods for assessing the water absorption capacity of rocks. To investigate the controlling factors of rock water absorption capacity, sandstone with different degrees of weathering collected from the Yungang Grottoes were selected as the study material. Nuclear magnetic resonance (NMR) technology was employed to test the porosity and pore size distribution of rock samples, and to establish the relationship between the free water absorption rate of sandstone and its density, porosity, and pore size. The results indicate that there is a linear relationship between the free water absorption rate and the density of sandstone, with the slope of the relationship being influenced by the degree of weathering. Additionally, the free water absorption rate of the sandstone is positively correlated with porosity and the proportion of small pores (0.1－1.0 μm), with porosity being the primary controlling factor and pore structure being the secondary controlling factor. This study deepens our understanding of the mechanisms controlling the water absorption of weathered sandstone. Furthermore, since wave velocity is also influenced by porosity and pore structure, a good linear relationship was observed between the free water absorption rate and wave velocity. Therefore, it is suggested that the free water absorption rate of rock mass can be estimated by in-situ testing of wave velocity.